Impact of destruction – Introduction to the Josephus Seminar, Theological University Kampen - Bekkum, Koert van (HTS teologiese studies, 2015)
This is an introduction to the contributions of Jan Willem van Henten and William den Hollander to the Josephus Seminar ‘Impact of destruction. Methodological questions in the study of Jewish and Christian reactions to the demolition of the Temple’ held at the Theological University in Kampen, the Netherlands. The introduction sketches the status quaestionis and the methodological issues in comparing the works of Josephus and the Gospels in reconstructing the impact of the destruction of the Temple in AD 70 on Judaism and Early Christianity.